PERAN ORANG TUA SEBAGAI NON-DIRECT SERVICE DALAM BIMBINGAN DAN KONSELING KOMPREHENSIF - Gumilang, Galang Surya (JURNAL FOKUS KONSELING, 2017)
This article describes and discusses a comprehensive guidance and counseling, the role of parents as the non-direct service in a comprehensive guidance and counseling to create a supportive environment for students. In a comprehensive guidance and counseling, the role of parents is vital for counselors provide guidance and counseling services in school. Counselors surrender completely to the role of parents implementing of guidance and counseling services at home. Parents have a stake as a non-direct service by monitoring the development of children in the home as well as coordinate with the counselor to provide information such as progress reports of children (students).